OBSERVACIONES PRELIMINARES DE LA CONDUCTA DE VISITA DE CENTRIS RODOPHTHALMA PÉREZ (HYMENOPTERA: ANTHOPHORIDAE) SOBRE ESPECIES DE ADESMIA (FABACEAE) EN LA IV REGIÓN DE CHILE - Chiappa, Elizabeth; Rodríguez, Sharon (Acta Entomológica Chilena, 2022)
At three locations of the IV Región of Chile (Andacollito, Hurtado and Varillar) a study was carried out to determine the visit behavior of Centris rodophthalma on Adesmia glutinosa and A. pedicellata (Fabaceae). Two flower characters, the number of open flowers and the néctar volume were recorded and related with behavioral aspects of the bee: visitation frequency, the time spent at flowers and searching time (refers to the time spent outside of the bushes). To examine relations between those parameters an analysis of stepwise múltiple regression was performed. Results of this analysis show that at Varillar, the visit frequency is determined by the néctar of A. glutinosa and the time spent on flowers is resolved when both parameters are acting together. At Andacollito, the visitation frequency and the time spent on flowers are determined by flower characters as a whole, but the time spent on flowers is also related to the number of open flowers of A. pedicellata. At Hurtado, the visitation frequency was explained by action of the variables conjointly and the time spent at flowers is also related to the number of open flowers. At the three places the néctar volume and number of flowers did not influence the searching time because this is shared, probably, with other functions like mating, resting, etc. The results suggest variability of visitation behavior at population level.